1997
DOI: 10.1182/blood.v90.7.2796.2796_2796_2803
|View full text |Cite
|
Sign up to set email alerts
|

The Human Antibacterial Cathelicidin, hCAP-18, Is Synthesized in Myelocytes and Metamyelocytes and Localized to Specific Granules in Neutrophils

Abstract: hCAP-18 is the only human member of the antibacterial and endotoxin-binding family of proteins known as cathelicidins. The antibacterial and endotoxin binding domains reside in the C-terminal 37 amino acids of the protein (LL-37) and this is believed to be unleashed from the neutralizing N-terminus by proteases from peroxidase positive granules. In human neutrophils, peroxidase positive and peroxidase negative granules can be subdivided into granule subsets that differ in protein content and ability to be exoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 53 publications
3
60
0
3
Order By: Relevance
“…Increased levels of AMPS (e.g., α defensins) have been observed in other body fluids (e.g., plasma) following a circulating neutrophila (Shiomi et al, 1993). The variation in the responses of different AMPs to prolonged exercise (Davison et al, 2009;Davison and Diment, 2010), therefore, may be due to the changes in the maturity of circulating neutrophils (as expressions of AMPs can vary throughout the maturation of the neutrophil in the bone marrow) or decreases in some AMPs may merely reflect neutrophils undergoing a refractory period post exercise (Cowland et al, 1995;Borregard and Cowland, 1997;Gullberg et al, 1997;Nagaoka et al, 1997;Sorensen et al, 1997;Nagaoka et al, 1998Nagaoka et al, , 2000Peake, 2002).…”
Section: Mucosal Immunity and Acute Exercisementioning
confidence: 99%
“…Increased levels of AMPS (e.g., α defensins) have been observed in other body fluids (e.g., plasma) following a circulating neutrophila (Shiomi et al, 1993). The variation in the responses of different AMPs to prolonged exercise (Davison et al, 2009;Davison and Diment, 2010), therefore, may be due to the changes in the maturity of circulating neutrophils (as expressions of AMPs can vary throughout the maturation of the neutrophil in the bone marrow) or decreases in some AMPs may merely reflect neutrophils undergoing a refractory period post exercise (Cowland et al, 1995;Borregard and Cowland, 1997;Gullberg et al, 1997;Nagaoka et al, 1997;Sorensen et al, 1997;Nagaoka et al, 1998Nagaoka et al, , 2000Peake, 2002).…”
Section: Mucosal Immunity and Acute Exercisementioning
confidence: 99%
“…For instance, Paneth cells in the small intestine release AMPs-rich granules upon stimulation by cholinergic or bacterial stimuli, 228 and granulocytes are known to contain AMPs in granules destined for extracellular secretion. 229,230 Therefore, as the synthesis and secretion of large AMPs may not be constitutive but amenable to induction by microbial macromolecules and inflammatory cytokine stimuli, several other large AMPs may yet to be catalogued. Hence, exploration of novel large antimicrobial human peptides is an ongoing work that may yield novel therapeutic agents.…”
Section: H Large Antimicrobial Human Peptidesmentioning
confidence: 99%
“…In addition to expression in epithelial tissues, cathelicidin is also produced by cells of the innate immune system [65,66]: human neutrophils [66,67], natural killer (NK) cells [68], dendritic cells [69], monocytes/macrophages [70,71], lymphocytes [72], mast cells [73], mesenchymal stem cells [39], and bone marrow stroma [74]. Lowry et al showed a hierarchy of expression of hCAP18 in freshly isolated peripheral blood-derived cells with low levels in lymphocytes, intermediate levels in monocytes, and the highest levels found in neutrophils.…”
Section: Expressionmentioning
confidence: 99%